Literary Forgery and the Monothelete Controversy: Some Scrupulous Uses of Deception - Susan Wessel (Greek, Roman, and Byzantine Studies, 2006)
At the Sixth Ecumenical Council (A.D. 680), conflicting assessments of texts were argued, and these debates, documented in the acts of the council, illuminate theories of authenticity and authorship in late antique Christianity.